Affective Domain and Foreign Language Learning: A Bibliometric Analysis - St. Asmayanti. Am; St. Asriati Am (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The affective domain, which includes emotions, motivation, attitudes, and values, plays a crucial role in shaping learning outcomes in foreign language education. Yet, much of the existing research investigates these factors in isolation, providing only a limited understanding of how they interact and influence second language acquisition as a whole. This study aims to map the evolution of research on the affective domain in foreign language learning from 2019 to 2023 through a comprehensive bibliometric analysis. Data were retrieved using the Publish or Perish software with Google Scholar as the database, yielding 231 publications. After applying defined inclusion and exclusion criteria, 149 documents were retained for analysis, consisting of 121 journal articles and 28 books. Bibliographic information was managed with Mendeley Reference Manager and analyzed using VOSviewer version 1.6.19 to generate visualizations of co-authorship, citation networks, and keyword co-occurrence. The results show that enjoyment, motivation, and anxiety remain central themes, with enjoyment increasingly highlighted as a facilitating factor for learner achievement. Citation analysis identified highly influential works on grit, classroom emotions, and emotional intelligence, reflecting the field’s growing alignment with positive psychology and social and emotional learning frameworks. Co-word analysis revealed five major thematic clusters: learner enjoyment and achievement, domain comparisons across Bloom’s taxonomy, emotional learning practices, integration of affective constructs into SLA frameworks, and systematic reviews of the field. Temporal analysis indicated a shift from general theoretical discussions prior to 2020 toward more empirical, context-specific, and measurement-based studies after 2021. This study contributes to the literature by clarifying thematic directions, identifying research gaps, and positioning the affective domain as a central element of second language acquisition.